Conservation of genetic resources of subfamily Bovinae by the establishment of a cryo-bank (European Bison Conservation Newsletter, 2012)
Conservation of genetic resources is connected with numerous problems which solution is crucial for the success of the entire program. At present the only effective method of long-term conservation of genetic material is its deep freezing in liquid nitrogen at -196°C. Some positive results were also obtained with the use of liquid oxygen which allows the use of lower temperatures. Cryo-conservation of sex cells of representatives of the Bovinae subfamily is widely applied in breeding practices. Experiences in cryo-preservation of sex cells of the European bison (Bison bonasus) and yak‘s (Bos mutus) are discussed.
Keywords: Bovinae; European bison; yak; sperm; semen cryopreservation; electro-ejaculation; male sex cells; cryo-banks